Doveweed (Murdannia nudiflora) Response to Environmental Resource Availability and Cultural Practices. Issue 2 (25th March 2019) - Atkinson, Jeffrey L.; McCarty, Lambert B.; Yelverton, Fred; McElroy, Scott; Bridges, William C.
Abstract: Susceptibility of a system to colonization by a weed is in part a function of environmental resource availability. Doveweed [ Murdannia nudiflora (L.) Brenan] can establish in a variety of environments; however, it is found mostly in wet or low-lying areas with reduced interspecies competition. Four studies evaluated the effect of mowing height, interspecies competition, and nitrogen, light, and soil moisture availability on M. nudiflora establishment and growth. A field study evaluated the effect of mowing height on M. nudiflora establishment. In comparison with unmowed plots, mowing at 2 and 4 cm reduced spread 46% and 30%, respectively, at 9 wk after planting. Effect of mowing height and nitrogen fertilization on 'Tifway' bermudagrass ( Cynodon dactylon Burtt-Davy× C. transvaalensis L. Pers.) and M. nudiflora interspecies competition was evaluated in a greenhouse trial. Murdannia nudiflora coverage was 62% greater in flats maintained at 2.6 cm than flats maintained at 1.3 cm. Supplemental application of 49 kg N ha −1 mo −1 increased M. nudiflora coverage 75% in comparison with 24.5 kg N ha −1 mo −1 . A difference in M. nudiflora coverage could not be detected between flats receiving 0 and 24.5 kg N ha −1 mo −1, suggesting moderate nitrogen fertilization does not encourage M. nudiflora colonization. Effect of light availability on M. nudiflora growth and development was evaluated in a greenhouse study. Growth in a 30%, 50%, or 70% reduced light environment (RLE) did not affect shoot growth on a dry weight basis in comparison with plants grown under full irradiance; however, internode length was 28% longer in a 30% RLE and 39% longer in a 50% and 70% RLE. Effect of soil moisture on M. nudiflora growth and development was evaluated in a greenhouse study. Plants maintained at 50%, 75%, and 100% field capacity (FC) increased biomass>200% compared with plants maintained at 12.5% or 25% FC.